Jeffektivnost' sorevnovatel'noj dejatel'nosti velosipedistov vysokoj kvalifikacii v zavisimosti ot urovnja funkcional'noj podgotovlennosti - Kolchynska, A. (Science in Olympic Sport, 2019)
Objective. Study of the competitive activity efficiency of highly skilled cyclists in the individual 4km pursuit race on track depending on the general level of functional fitness and the degree of development of its leading structural factors. Methods. Analysis of scientific and methodological literature, complex physiological testing, ergometers, pulsometry, spirometry, gas analysis, methods of mathematical statistics. Results. To determine the possible result that an athlete can demonstrate at the achieved fitness level, a comprehensive physiological examination is conducted and its results are compared with those of the examination of fitness level of the athletes participating in the major international competitions in the individual 4km pursuit race on track and with those of competitive distance covering. The highest sports results were registered in cyclists with a general level of functional fitness of 70-80%. At 55-60% functional fitness level, athletes displayed relatively low sports results while covering 4 km distance on the track. At the same time, athletes can demonstrate the same sports result at different ratio of the degree of development of the leading structural factors of functional fitness. Conclusions. Efficient design of the training process of cyclists necessitates assessment of the level of their functional fitness and the degree of development of its leading structural factors and comparison of the obtained examination results with the normative values for highly skilled athletes. To determine the possible sports result, it is necessary to use graphical dependencies of their changes among them.